Fire exposure index as a tool for guiding prevention and management - De Freitas, Ana; Ferreira, Joice; Escada, Maria; Reis, João; Leite, Cândida; Andrade, Dárlison; Spínola, Jackeline; Soares, Maria; Anderson, Liana (Frontiers in Physics, 2023)
Protected Areas (PA) in Brazil have legal instruments for the conservation and protection of fauna and flora. The Sustainable Use Reserves (SURs) category have mechanisms to ensure the security of traditional lifestyles. Despite the existence of mechanisms and information that contribute to the protection of forest areas, threats to its conservation such as deforestation, fires, and climate extremes are increasing. Fires represent a major threat to many sustainable development goals, such as climate, health and food security, especially for people who depend on forest resources. This study covers two SURs, the Tapajós National Forest (FLONA Tapajós) and the Tapajós-Arapiuns Extractive Reserve (RESEX Tapajós-Arapiuns) located in Pará State, Brazilian Amazon, where deforestation, fires and land conflicts have escalated during the last decade. This research aimed to analyze environmental and land management data to construct a Fire Exposure Index (FEI), identify the pressure exerted on SURs and a tool to guide strategic planning since exposure is a component of vulnerability, therefore also of risk. The index is composed of four dimensions: fire, landscape, climate and territorial management. We analyzed the spatio-temporal dynamics between 2003 and 2020 to determine the FEI in 2020. The results indicate where and how interactions occur in priority areas, with regard to fire, landscape, climate and territorial management. High values of FEI (above 0.8) were mainly distributed around the northern and southeastern part of FLONA Tapajós in approximately 1,300 km², an area occupied by a high density of roads and agricultural expansion, which may affect the interior of the SURs. In the RESEX Tapajós-Arapiuns, the area with high FEI occurs along the banks of the Arapiuns and Tapajós rivers, covering an area of about 330 km², where most of the riverside communities live. The methodology developed in this research is potentially replicable for other protected areas in Brazil and in the world to support understanding and the development of management strategies to deal with fire threats. The additional format of communicating the results of this research to society and decision makers was conceived as a dashboard to facilitate its use.